Total and horizontal distances of the foveal stereotaxic displacement can be prognostic indicators for patients with idiopathic epiretinal membrane - Zhang, Zhengxi; Mao, Jianbo; Lao, Jimeng; Chen, Nuo; Deng, Xinyi; Chen, Yijing; Tao, Jiwei; Chen, Yiqi; Shen, Lijun (Frontiers in Medicine, 2023)
Introduction: This study aimed to examine the foveal stereo deviations in the different ectopic inner foveal layer (EIFL) stages of idiopathic epiretinal membrane (iERM) and assess its predictive utility for the baseline and postoperative best-corrected visual acuity (BCVA). Methods: Based on the calculational combination of foveal displacements in the horizontal and vertical axial optical coherence tomography (OCT) images, the foveal stereotaxic displacement was estimated through the total distance (TD, the distance from the foveal bottom to the inner edge of displaced central foveal) and horizontal distance (HD, projection of the TD in the retinal plane). The preoperative TD, HD, and other OCT- and OCT angiography (OCTA)-related indicators were obtained. The correlations between structural parameters and baseline and postoperative BCVA were evaluated through correlation and multiple linear regression analyses. Results: In patients with advanced EIFL stage, there was a significant increase in the HD, TD, baseline log of the minimum angle of resolution unit for BCVA, central macular thickness (CMT), acircularity index, and incidence of microcystic macular edema (MME) (P < 0.05). Further, they showed a decreased foveal avascular zone (FAZ) area and perimeter (P < 0.001). HD, TD, CMT, MME, FAZ area, and FAZ perimeter were significantly correlated with the baseline and postoperative BCVA (P < 0.05). TD had the highest correlation indexic and was an individual predictor of the baseline and postoperative BCVA. Moreover, FD-300 and MME were individual predictors of postoperative BCVA. Discussion: Stereoscopic foveal deviations significantly correlated with the baseline and postoperative visual acuity. TD may be used as an independent prognostic factor for BCVA.